Venture capital law in China - Lin, Lin ca. 20./21. Jh (International corporate law and financial market regulation, 2021)
China's venture capital market is not just the world's largest and fastest developing market, it also has the unique distinction of being engineered through heavy governmental intervention. This book breaks new ground by examining and testing established legal theories regarding the law of venture capital through the lens of the Chinese venture capital market. Using a hand-collected dataset of venture capital agreements, interviews with practitioners, and Chinese court judgements, it provides a comprehensive and insightful analysis of the Chinese venture capital market from the legal perspective. Topics covered include the roles of law and governmental intervention in developing the market, the state of investor protection, unique contractual developments and exits of venture capital investments. By providing an in-depth comparative analysis against the American venture capital market, it provides critical context and makes the Chinese venture market accessible. It is an invaluable resource for venture capital scholars, policymakers and practitioners